Can Perceptions of an Individual's Organizational Citizenship Be Influenced Via Strategic Impression Management Messaging?. (January 2019) - Adame, Elissa Arterburn; Bisel, Ryan S.
A two-part investigation explored whether strategic messaging can influence others' perceptions of one's organizational citizenship. In a first study, inductive analysis of interviews ( N = 24) revealed working adults hold implicit rules for how (and how not) to present themselves to their colleagues as good citizens: The rules require organizational members' attempt to avoid being interpreted by colleagues as motivated by personal gain or working through ostentatious means. Then, the content of impression management (IM) messages were crafted—based on these rules—and used for a message-processing experiment ( N = 274). Analysis demonstrated working adults' perceptions of organizational citizenship behavior were influenced by strategic self- and other-referential messaging regarding motives and means. Results imply that strategic IM messaging, which conforms to the rules of organizational citizenship behavior impression-construction, are rewarded with audience perceptions of being citizenly. Implications for IM in the workplace are discussed.